Risk factors associated with Salmonella in dairy cattle farms in Henan and Hubei provinces, China - Jie Wang; Xiaojie Zhu; Yuxi Zhao; Yongkang Xue; Zhen Zhang; Lei Yan; Yingyu Chen; Ian D. Robertson; Aizhen Guo; Joshua W. Aleri (BMC, 2023)
Abstract A cross-sectional study was conducted to evaluate the risk factors associated with the Salmonella infection status of dairy herds in Henan and Hubei provinces, China. Herds were assigned a Salmonella status based on the isolation of Salmonella from fecal samples obtained from adult lactating dairy cows. Information on potential biosecurity risk factors was collected using a questionnaire template via a 15-min face-to-face interview with dairy cattle producers from May 2020 to March 2021. The questionnaire consisted of 23 questions across two broad categories of potential biosecurity risk factors: farm and biosecurity managemental factors. A total of 48 farms were surveyed. In all (100%, 48/48) of the surveyed farms, although sick animals were separated from healthy animals using fencing, there were no strict quarantine protocols for newly introduced animals. Mixed species rearing was practiced in 35.4% (17/48) of the farms. Feces were removed more than once a day in 45.8% (22/48) of the farms, whereas the remainder (54.2%, 26/48) only removed animal feces once a day. A total of 29.2% (14/48) of the farms were located < 2 km from other livestock farms. The use of personal protective equipment was consistently performed on all farms, with a majority of the workers on most farms (81.3%, 39/48) always disinfecting footwear before entering production areas. A significant association between Salmonella-positive status and the high frequency of the presence of wildlife (birds and rodents in sheds and feed storage places) was recorded (OR: 11.9, 95% CI: 1.7, 84.1, p = 0.013). Fortunately, no farms shared farm equipment with other farms. The study highlights the occurrence of wildlife as a risk factor for the presence of Salmonella in investigated dairy herds. There is a need to institute appropriate on-farm control measures for wild birds and rodents to control the potential spread of Salmonella in dairy production systems.